Methods of measuring migration - Irbid Governorate as a model - Marie, Ibtisam Mahmoud Amin; Almanasieh, Nazih Ibrahim (Journal of Humanities & Social Sciences, 2023)
The study aimed to measure the size of internal population migration in main ways and measure its impact on the growth of urban centers in Irbid governorate during the period 2004-2015. The study reached a set of results: that there is no clear difference between the results of measuring migration in several ways in the years 2004 and 2015; The results of internal migration show the rate of net migration by the method of balancing that the migration trend was positive in the Al-Qasaba and Bani Obeid districts due to its adhesion to a network of roads with the center of the governorate from the southern end in 2015, and the net migration was negative in the rest of the districts. In 2004, however, the net migration rate was positive only in the Kasbah district. As a result of the use law of gravity, it was associated with the element of distance in estimating the size of incoming and outgoing migration, and by comparing the actual and estimated volume of incoming and outgoing immigration, we find a difference in the pattern of immigrants’ distribution, as the model relied on the size of immigrants, while the real size depended on the civil registry data of the Civil Status Department for each major General. With different methods of measuring migration mathematically, they all proved effective in determining areas of attraction and expulsion, and finding net, incoming and outgoing migration rates. It was also shown from the spatial distribution pattern of immigrants according to population density that the largest districts in terms of the distribution of the Syrian population in 2015 were concentrated in four districts of Urban, Al-Qasaba, Al-Ramtha, Bani Obeid and Al-Koura, and the percentage of population concentration reached (72%) of the total Syrian population in the governorate The percentage of rural districts was 37% of their total in the governorate. Therefore, we find that the population density of Syrians in the Al-Qasaba district was the highest, while the Al-Mazar, Al-Wasatiya and Al-Taybeh districts formed the average population density due to their small area. As for the Bani Obeid and Al-Ramtha districts, the population densities increased as a result of the Al-Ramtha district’s proximity to the Syrian border, which constituted a passage for them from their lands towards Jordan. As for the Bani Obeid, as a result of its direct adherence to the Kasbah districts.